Enzymatic Glycosylation of Nonbenzoquinone Geldanamycin Analogs via Bacillus UDP-Glycosyltransferase - Wu, Cheng-Zhu (American Society for Microbiology, 2012)
Geldanamycin (GM) is a naturally occurring anticancer agent isolated from several strains of Streptomyces hygroscopicus. However, its potential clinical utility is compromised by its severe toxicity and poor water solubility. For this reason, considerable efforts are under way to make new derivatives that have both good clinical efficacy and high water solubility. On the other hand, glycosylation is often a step that improves the water solubility and/or biological activity in many natural products of biosynthesis. Here, we report the facile production of glucose-conjugated nonbenzoquinone GM analogs using the Bacillus UDP-glycosyltransferase BL-C. Five aglycon substrates containing nonbenzoquinone aromatic rings were chosen to validate the in vitro glycosylation reaction. Putative glucoside compounds were determined through the presence of a product peak(s) and were also verified using LC/MS analyses. Further, the chemical structures of new glucoside compounds 6 and 7 were elucidated using spectroscopy data. These glucoside compounds showed a dramatic improvement in water solubility compared with that of the original aglycon, nonbenzoquinone GM.